The Streaming Television Industry: Mature or Still Growing? - Snyman, Johannes H.; Gilliard, Debora J. (Journal of Marketing Development and Competitiveness, 2019)
This paper is about the streaming television industry. It begins by defining the industry and provides a brief history of the television industry in general, from the first transatlantic television signal in 1928 to 2018. From that point, it emphasizes the streaming television industry, which started in 2007, when Netflix first streamed movies over the internet. The main section of the paper focuses on Michael Porter’s theory of the industry life cycle to determine the current stage of the industry. The research question is developed, proposing that the industry is in the growth phase. Then, the number of paid subscribers of the top streaming providers in 2018 is used to address the research question. The results indicate that the industry is in the growth phase. The final section provides an outlook for the industry’s future.